2022
DOI: 10.3389/fonc.2021.801506
|View full text |Cite
|
Sign up to set email alerts
|

ASF1B Serves as a Potential Therapeutic Target by Influencing Cell Cycle and Proliferation in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors with high morbidity and mortality. Therefore, it is very important to find potential biomarkers that can effectively predict the prognosis and progression of HCC. Recent studies have shown that anti-silencing function 1B (ASF1B) may be a new proliferative marker for tumor diagnosis and prognosis. However, the expression and function of ASF1B in hepatocellular carcinoma remain to be determined. In this study, integrated analysis of the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Preliminary evidence suggests that m6A/m1A/m5C regulated genes play important biological roles in the progression of HCC, which can be used to determine the prognosis and survival of HCC patients. The signaling pathways, including the cell cycle, DNA replication, and WNT are closely associated with cancer progression (28)(29)(30)(31)(32)(33)(34). Previous studies have found that ASF1B is highly expressed in HCC, and elevated ASF1B expression level is associated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary evidence suggests that m6A/m1A/m5C regulated genes play important biological roles in the progression of HCC, which can be used to determine the prognosis and survival of HCC patients. The signaling pathways, including the cell cycle, DNA replication, and WNT are closely associated with cancer progression (28)(29)(30)(31)(32)(33)(34). Previous studies have found that ASF1B is highly expressed in HCC, and elevated ASF1B expression level is associated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways, including the cell cycle, DNA replication, and WNT are closely associated with cancer progression ( 28 34 ). Previous studies have found that ASF1B is highly expressed in HCC, and elevated ASF1B expression level is associated with poor prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASF1B has also been shown to play a role in the formation of lung adenocarcinoma tumors, and it was discovered that ASF1B may promote tumor growth by regulating the intermediate protein BCAR1 ( 35 ). Additionally, another study pointed out that the oncogene ASF1B may be the target of inhibiting the growth of hepatocellular carcinoma cells ( 36 ). Thus, ASF1B may participate in glioma tumorigenesis by regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…ASF1B has been shown to play a role in the formation of lung adenocarcinoma tumors, and it was discovered that ASF1B may promote tumor growth by regulating the intermediate protein BCAR1 (35). Additionally, another study pointed out that the oncogene ASF1B may be the target of inhibiting the growth of hepatocellular carcinoma cells (36). Thus, ASF1B may participate in glioma tumorigenesis by regulating cell proliferation.…”
Section: Discussionmentioning
confidence: 99%